Capacity of public health laws enforcement by health inspectors in state of Selangor, Malaysia - Syed Mohamed Aljunid,; Sharifa Ezat Alkaff, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
A cross sectional study initiated among the Public Health Enforcement Inspectors in state of Selangor, Malaysia in July 2003 using a self administered questionnaire and universal sampling with the purpose to determine the capacity of public health laws enforcement and factors influencing it. A total of 99 respondents from the Health Districts Ofices and I00 respondents from the Local Municipal Health Departments participated in this study. It was found that the level of enforcement is generally low in all the units except for two units; the Food Unit and Sanitary and Hygiene Units. Factors found to influence enforcement capacity are the units' the enforcers work in and the length of service being in the same unit. Further analysis using multiple logistic regression, showed that respondents from the Food Unit (adjusted odds ratio 22; CI 95% : 7.851, 58.896), enforcers from the middle level category (adjusted odds ratio 5; CI 95%: 1.397, 17.630), duration of service of 4 years and above in the same unit (adjusted odds ratio 6; CI 95%: 2.174, 13.747), past acceptance of formal service rewards from their departments (adjusted odds ratio 3; CI 95% : 1.150, 6.917); low exposure to bribery (adjusted odds ratio 46; CI 95% : 2.336, 1000) and have in the past being oflered bribes while on the field (adjusted odds ratio 3; CI 95% : 1.018, 4.772) are associated with higher enforcement capacity. In conclusion; die attention must be looked into the enforcement organization with respect to the duration of service, acknowledgement via service rewards and monitoring of bribes exposure will help shape a better public health laws' enforcement capacity.